2010
DOI: 10.1111/j.1570-7458.2010.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of metals and metalloids on insect behavior

Abstract: In toxicology studies, the use of death as an endpoint often fails to capture the effects a pollutant has on disruptions of ecosystem services by changing an animal's behavior. Many toxicants can cause population extinctions of insect species at concentrations well below the EC 25 , EC 50 , or EC 90 concentrations traditionally reported from short-term bioassays. A surprising number of species cannot detect metal and metalloid contamination, and do not always avoid food with significant metal concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 99 publications
(146 reference statements)
5
48
1
2
Order By: Relevance
“…These characteristics indicate that this population has potential as a cadmium hyperaccumulator. Our findings of between-population variation in accumulation are consistent with previous research that has demonstrated that cadmium accumulation varies widely between populations [55], and that cadmium hyperaccumulation may be a population-specific rather than species-wide trait [25]. To our knowledge, there is no current available information about the distribution or presence of partridge pea populations in cadmium-contaminated soils.…”
Section: Discussionsupporting
confidence: 91%
“…These characteristics indicate that this population has potential as a cadmium hyperaccumulator. Our findings of between-population variation in accumulation are consistent with previous research that has demonstrated that cadmium accumulation varies widely between populations [55], and that cadmium hyperaccumulation may be a population-specific rather than species-wide trait [25]. To our knowledge, there is no current available information about the distribution or presence of partridge pea populations in cadmium-contaminated soils.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accord with Morgen and Trumble (2010), indicating that high metal concentrations frequently lead to modified ingestion, locomotor and reproductive disturbances (decreased egg laying and reduced fitness of offspring). However, C. vicina can be classified as a heavy metal-tolerant insect, with adaptations enabling to tolerate exposure to relatively high concentrations of some heavy metals (Gall et al, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Zinc, known to negatively affect insect feeding and behavior (Mogren & Trumble, 2010), had a negative effect on leaf consumption by O. sulcatus in our study. It was not demonstrated whether such relationships hold true in no-choice situations, but the fact that blackcurrant had the highest concentrations of C and Zn, two conditions known to negatively affect insect performance (Awmack & Leather, 2002;Mogren & Trumble, 2010), is compatible with it being an inferior host in which plant chemistry was influencing O. sulcatus. It was not demonstrated whether such relationships hold true in no-choice situations, but the fact that blackcurrant had the highest concentrations of C and Zn, two conditions known to negatively affect insect performance (Awmack & Leather, 2002;Mogren & Trumble, 2010), is compatible with it being an inferior host in which plant chemistry was influencing O. sulcatus.…”
Section: Discussionmentioning
confidence: 43%